ANALISIS KEBUTUHAN TENAGA PERPUSTAKAAN UNIVERSITAS TRIJAYA NUSAMEDIA - Danang Dwijo Kangko; Erika Erika (Perpustakaan Nasional RI, 2017)
Library staff is regulated under the Library Act number 43 of 2007, and in the standard of higher education library implementation. Managing the library staff is one of the elements in the library management process. Problems in this library staff management can disrupt the service and operation of the library. The need of library staff is to be planned by considering quantity and qualifications. In the previous study of Trijaya Nusamedia University Library (pseudonym), problems related to library staff were discussed. This raised a question about the availability of library staff in Trijaya Nusamedia University Library. This study was conducted to determine the ideal number of library staff (librarians and library technician staff) needed in Trijaya Nusamedia University Library by analyzing it using an adoption of Ranganathan 's formula based on the condition of the library. The results of the study showed that the number of library staff in Trijaya Nusamedia University Library was still not ideal.